Age-related changes in the temporal dynamics of executive control: a study in 5- and 6-year-old children - Lucenet, Joanna; Blaye, Agnès (Frontiers in Psychology, 2014)
Based on the Dual Mechanisms of Control theory (Braver, Gray & Burgess, 2007), this study conducted in 5- and 6-year-olds, tested for a possible shift between two modes of control, proactive vs. reactive, which differ in the way goal information is retrieved and maintained in working memory. To this end, we developed a children-adapted version of the AX-Continuous-Performance Task (AX-CPT). Twenty-nine 5-year-olds and twenty-eight 6-year-olds performed the task in both low and high working-memory load conditions (corresponding respectively to a short and a long cue-probe delay). Analyses suggested that a qualitative change in the mode of control occurs within the 5-year-old group. However, quantitative, more graded changes were also observed both within the 5-year-olds, and between 5 and 6 years of age. These graded changes demonstrated an increasing efficiency in proactive control with age. The increase in working memory load did not impact the type of dynamics of control, but had a detrimental effect on sensitivity to cue information. These findings highlight that the development of the temporal dynamics of control can be characterized by a shift from reactive to proactive control together with a more protracted and gradual improvement in the efficiency of proactive control. Moreover, the question of whether the observed shift in the mode of control is task dependant is debated.